Low-melting-point antibacterial alkali-free glass and preparation method thereof
By using low-melting point antibacterial and alkali-free glass formula and overflow method in TFT substrate glass, the problems of high melting point and insufficient antibacterial performance of traditional TFT substrate glass raw materials are solved, and glass preparation with low energy consumption, low cost and high antibacterial performance are achieved , improve product quality and storage time.
Patent Information
- Application Number
- CN202411307157.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-19
- Publication Date
- 2024-12-27
AI Technical Summary
The high melting point of traditional TFT substrate glass raw materials leads to large energy consumption and insufficient antibacterial performance, which poses a risk of growing mold and affects production efficiency and product quality.
It adopts a low-melting point antibacterial and alkali-free glass formula, including silica, alumina, boric acid, magnesium oxide, carbonate, nitrate, tin oxide, titanium trifluoride and antibacterial enhancer, and is prepared by high-temperature melting and overflow method. Form low melting point antibacterial glass.
It significantly reduces the glass manufacturing temperature, reduces energy consumption and production costs, improves antibacterial performance, extends storage time, reduces quality risks in downstream processing processes, and improves the chemical stability and optical properties of the glass.
Smart Images

Figure CN119191705A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of glass, and in particular to a low-melting-point antibacterial alkali-free glass and a preparation method thereof. Background Art
[0002] In the field of electronic glass manufacturing, the melting point of raw materials directly affects the energy consumption, production cost and production efficiency of the product during the production process. In the traditional electronic glass manufacturing process, raw materials such as quartz sand and alumina have high melting points, which results in a large amount of energy consumption during the raw material melting process, increasing production costs, and the high melting point requires higher heat resistance of the kiln channel. Therefore, how to reduce the melting point of glass raw materials has become a technical problem that the industry needs to solve urgently.
[0003] On the other hand, although traditional TFT substrate glass has excellent physical and chemical properties, it is deficient in antibacterial properties and is prone to mold growth, which poses a major quality risk in subsequent downstream processing. Therefore, developing a TFT substrate glass that has both low melting point characteristics and antibacterial functions has become a new trend in the industry. Summary of the invention
[0004] The technical problem to be solved by the present invention is: to overcome the shortcomings of the prior art, to provide a low-melting-point antibacterial alkali-free glass and a preparation method thereof, to solve the problems of high melting point and high energy consumption of traditional TFT substrate glass raw materials, to meet the market demand for the antibacterial properties of TFT substrate glass, and to provide an innovative technical solution for the electronic glass manufacturing industry.
[0005] The technical solution of the present invention is:
[0006] On the one hand, the present invention provides a low-melting-point antibacterial alkali-free glass, comprising the following components in mass percentage: 60-75% silicon dioxide, 3-13% aluminum oxide, 3-6% boric acid, 1.5-5% magnesium oxide, 0.7-7.5% carbonate, 0.5-3% nitrate, 0.01-0.5% tin oxide, 0.1-5% titanium trifluoride and 0-1% antibacterial enhancer.
[0007] Preferably, the antibacterial enhancer is nano silver particles or nano titanium dioxide.
[0008] Preferably, the carbonate comprises 0.2-5% calcium carbonate and 0.5-2.5% barium carbonate.
[0009] Preferably, the nitrate is strontium nitrate.
[0010] As the core component of liquid crystal display, the performance and quality of TFT glass substrate directly determine the display effect and service life of the display. TFT glass substrate is made of a variety of raw materials carefully proportioned, and each component has its unique function.
[0011] SiO2
[0012] Introduction method: Quartz sand, silicate is the main component of TFT glass substrate, usually introduced in the form of quartz sand. Quartz sand melts at high temperature and forms glass after mixing with other oxides.
[0013] Function: SiO2 is the skeleton element of the glass substrate. It forms an irregular continuous network with the structure of silicon-oxygen tetrahedron (SiO4), providing the substrate with excellent physical and chemical properties. SiO2 can reduce the thermal expansion coefficient and density of glass, increase the strain point and chemical stability of glass, and enable the substrate to maintain stable performance under high temperature and harsh environment.
[0014] Al2O3
[0015] Introduction method: Alumina powder. Alumina is an intermediate oxide and is added in the form of powder or compound during the glass manufacturing process.
[0016] Function: Al2O3 plays a role in filling the glass, which can increase the stability of the glass and reduce the thermal expansion coefficient of the glass. In addition, Al2O3 can significantly increase the strain point and elastic modulus of the glass and increase the chemical stability of the glass.
[0017] B2O3
[0018] Introduction: Boric acid, as a flux, is added in the glass manufacturing process in the form of powder or solution.
[0019] Function: B2O3 can reduce the melting viscosity of glass, making it easier to melt and form. A proper amount of B2O3 can also increase the chemical stability of glass (resistance to hydrofluoric acid). When the B2O3 content is too high, it will damage the acid resistance of the glass and reduce its strain point, so its content needs to be strictly controlled.
[0020] SrO, BaO, CaO
[0021] Introduction method: Strontium nitrate, barium carbonate, and calcium carbonate. These carbonates and nitrates are added in the form of compounds during the glass manufacturing process, and after high-temperature decomposition, oxides such as strontium oxide, barium oxide, and calcium oxide are introduced.
[0022] Function: Oxides such as strontium oxide, barium oxide and calcium oxide can adjust the density, linear expansion coefficient, strain point and chemical stability of glass. They have the characteristics of not increasing the density, not increasing the linear expansion coefficient, not reducing the strain point too much, and can also improve the solubility of glass. At the same time, strontium oxide also has the function of absorbing X-rays, which helps to protect the display from radiation damage. However, if added too much, it may cause defects such as bubbles and stones in the glass, and may also affect the optical properties and processing properties of the glass.
[0023] MgO, SnO2
[0024] Introduction: These oxides are usually added to the glass manufacturing process in the form of powders or compounds.
[0025] Function: As glass regulators and intermediate components, they can further optimize the performance of glass. For example, the thermal expansion coefficient and density of glass can be reduced by adding an appropriate amount of magnesium oxide (magnesium oxide has a high melting point and a stable crystal structure, which can increase the stability of the glass network structure and reduce the structural changes of the glass when the temperature changes, thereby reducing the thermal expansion coefficient. Magnesium oxide can also replace some components with a relatively large molecular weight, thereby reducing the overall density of the glass); tin oxide is a clarifier that can improve the transparency and purity of glass, replacing the raw material of toxic arsenic oxide; however, if the amount is too much, it may cause the melting temperature of the glass to increase, which is not conducive to the production process; too high a content will also destroy the network structure of the glass, causing more defects inside the glass, affecting the optical properties of the glass.
[0026] TiF3
[0027] Introduction method: Usually added to the glass manufacturing process in the form of powder or compound.
[0028] Function: As a flux and antibacterial agent, titanium trifluoride decomposes at high temperatures to produce fluoride, which helps to lower the melting point of glass raw materials. At the same time, fluoride ions and titanium ions have antibacterial effects.
[0029] Antibacterial enhancers can further enhance the antibacterial properties of glass.
[0030] On the other hand, the present invention provides a method for preparing the above-mentioned low-melting-point antibacterial alkali-free glass, wherein the components are mixed evenly and sent into a high-temperature melting furnace for melting, and then clarified, homogenized, formed and annealed to obtain the low-melting-point antibacterial alkali-free glass.
[0031] Overflow production principle
[0032] The basic principle of overflow method for producing TFT glass substrates is to introduce molten glass into the overflow tank. When the glass reaches the upper limit of the volume, it overflows from both sides of the overflow tank along the tube wall and converges at the bottom like a waterfall to form a sheet substrate. This process can produce ultra-thin glass substrates with double original glass surfaces, avoiding subsequent post-processing processes such as glass surface grinding or polishing, and improving production efficiency and product quality.
[0033] Processing process
[0034] (1) Raw material preparation
[0035] Prepare qualified glass raw materials: quartz sand (SiO2), alumina (Al2O3), boric acid (H3BO3), nitrate, carbonate, magnesium oxide, tin oxide, titanium trifluoride and antibacterial enhancer, mix them evenly after precise proportioning.
[0036] (2) Melting
[0037] The mixed raw materials are sent into a high-temperature furnace and melted at 1600°C to decompose titanium trifluoride and fully react with other raw materials. During the melting process, the temperature, atmosphere and other parameters in the furnace need to be strictly controlled to ensure the uniformity and stability of the glass liquid.
[0038] (3) Clarification and homogenization
[0039] Clarification: In a high-temperature melting furnace, the gas in the molten glass gradually gathers to form large bubbles under the action of the clarifier (tin oxide decomposes at high temperature to produce oxygen, and oxygen combines with other gases in the molten glass to form larger bubbles), and rises to the surface of the molten glass through buoyancy and is discharged from the melting furnace.
[0040] Homogenization: The clarified glass liquid will enter the homogenization equipment. The stirring paddle of the homogenization equipment rotates slowly under the drive of the motor to stir the glass liquid, so that the glass liquid in different areas mixes with each other and promotes the uniform distribution of components. The bubbler introduces gas into the glass liquid to form bubbles. The bubbles will drive the glass liquid to flow during the rising process, achieving the effect of homogenization.
[0041] (4) Overflow molding
[0042] The molten glass flows into the overflow trough through the platinum channel. When the glass reaches the upper limit of the overflow trough volume, under the action of gravity, the glass overflows from both sides of the overflow trough along the tube wall to form a continuous glass sheet. In overflow molding, the thickness and surface quality of the glass sheet can be accurately controlled by adjusting parameters such as flow rate and overflow trough size.
[0043] (5) Annealing
[0044] The formed glass sheet is heated to a certain temperature (usually near the transition temperature of the glass) to relax the stress inside the glass. Then, the temperature is gradually lowered at a certain cooling rate to gradually cool the glass to room temperature. By controlling the cooling temperature and time, the physical and chemical properties of the glass sheet can be adjusted.
[0045] (6) Post-processing and inspection
[0046] The annealed glass pieces are cut, the edges are ground and polished, and cleaned to remove edge burrs. At the same time, strict quality inspections are carried out to ensure that the glass pieces meet quality requirements.
[0047] (7) Packaging and storage
[0048] The glass pieces that have been processed and qualified by quality inspection are packaged and stored in a constant temperature, dry and clean environment.
[0049] Compared with the prior art, the present invention has the following beneficial effects:
[0050] The present invention adds titanium trifluoride to the glass formula to decompose fluoride ions and titanium ions at high temperature. The fluoride ions interact with other raw materials to form low-melting-point fluorides. The generated fluorides can also reduce the viscosity of the glass liquid, promote the melting and mixing of the raw materials, thereby reducing the melting point of the glass, significantly reducing the manufacturing temperature of the electronic glass, and reducing energy consumption and production costs. Fluoride ions and titanium ions also have excellent antibacterial and antiviral properties, can inhibit and kill a variety of bacteria and viruses, give electronic glass excellent antibacterial properties, extend the storage time, and reduce the quality risks in downstream processing technology. After adding an appropriate amount of titanium trifluoride to the raw materials, the chemical stability, mechanical strength and optical properties of the electronic glass are also improved to a certain extent. In addition, the addition of an antibacterial enhancer can further enhance the antibacterial properties of the glass and form a multiple antibacterial barrier. BRIEF DESCRIPTION OF THE DRAWINGS
[0051] Figure 1 It is a trend chart showing the melting point of the raw material mixed sample of the present invention as a function of the titanium trifluoride content in Examples 1-10 and the content of the key components in Comparative Examples 1-5.
[0052] Figure 2 It is a trend diagram showing the transmittance of the glass of the present invention in the visible light band (400-800 nm) as a function of the titanium trifluoride content in Examples 1-10 and the content of the key components in Comparative Examples 1-5.
[0053] Figure 3 It is a trend diagram of the refractive index of the glass of the present invention at 589.3 nm as a function of the titanium trifluoride content in Examples 1-10 and the content of the key components in Comparative Examples 1-5.
[0054] Figure 4 It is a trend diagram of the thermal expansion coefficient (0-300° C.) of the glass of the present invention as a function of the titanium trifluoride content in Examples 1-10 and the content of the key components in Comparative Examples 1-5.
[0055] Figure 5 It is a trend diagram of the softening point of the glass of the present invention as a function of the titanium trifluoride content in Examples 1-10 and the content of the key components in Comparative Examples 1-5.
[0056] Figure 6 It is a trend diagram of the annealing point of the glass of the present invention as a function of the titanium trifluoride content in Examples 1-10 and the content of the key components in Comparative Examples 1-5.
[0057] Figure 7 It is a trend diagram of the strain point of the glass of the present invention as a function of the titanium trifluoride content in Examples 1-10 and the content of the key components in Comparative Examples 1-5.
[0058] Figure 8 It is a trend diagram of the Young's modulus of the glass of the present invention as a function of the titanium trifluoride content in Examples 1-10 and the content of the key components in Comparative Examples 1-5.
[0059] Fig. 9 It is a trend diagram of the shear modulus of the glass of the present invention as a function of the titanium trifluoride content in Examples 1-10 and the content of the key components in Comparative Examples 1-5.
[0060] Fig.10 It is a trend diagram of the Poisson's ratio of the glass of the present invention as a function of the titanium trifluoride content in Examples 1-10 and the content of the key components in Comparative Examples 1-5.
[0061] Fig.11 It is a trend chart showing the chemical stability of the glass of the present invention as a function of the titanium trifluoride content in Examples 1-10 and the key components in Comparative Examples 1-5.
[0062] Fig.12 It is a trend chart showing the antibacterial rate of the glass of the present invention as a function of the titanium trifluoride content in Examples 1-10 and Comparative Example 2.
[0063] Fig.13 It is a comparison chart of the antibacterial rate of the glass of the present invention as the content of the key components in Comparative Example 1, Comparative Examples 3-5 and Examples 2-3 change. DETAILED DESCRIPTION
[0064] In order to enable persons skilled in the art to better understand the technical solution of the present invention, the technical solution of the present invention will be clearly and completely described below in conjunction with the embodiments of the present invention.
[0065] Example 1
[0066] The low-melting-point antibacterial alkali-free glass of this embodiment includes the following components in mass percentage: SiO2 67.65%, Al2O3 10.94%, H3BO3 5.97%, MgO 4.98%, CaCO3 3.98%, Sr(NO)2 2.99%, BaCO3 2.49%, SnO2 0.5%, and TiF3 0.5%.
[0067] Example 2
[0068] The low-melting-point antibacterial alkali-free glass of this embodiment includes the following components in mass percentage: SiO2 67.31%, Al2O3 10.89%, H3BO3 5.94%, MgO 4.95%, CaCO3 3.96%, Sr(NO)2 2.97%, BaCO3 2.48%, SnO2 0.5%, and TiF3 1%.
[0069] Example 3
[0070] The low-melting-point antibacterial alkali-free glass of this embodiment includes the following components in mass percentage: SiO2 67.11%, Al2O3 10.86%, H3BO3 5.92%, MgO 4.93%, CaCO3 3.95%, Sr(NO)2 2.96%, BaCO3 2.47%, SnO2 0.49%, and TiF3 1.3%.
[0071] Example 4
[0072] The low-melting-point antibacterial alkali-free glass of this embodiment includes the following components in mass percentage: SiO2 66.97%, Al2O3 10.84%, H3BO3 5.91%, MgO 4.93%, CaCO3 3.94%, Sr(NO)2 2.96%, BaCO3 2.46%, SnO2 0.49%, and TiF3 1.5%.
[0073] Example 5
[0074] The low-melting-point antibacterial alkali-free glass of this embodiment includes the following components in mass percentage: SiO2 66.85%, Al2O3 10.81%, H3BO3 5.9%, MgO 4.91%, CaCO3 3.93%, Sr(NO)2 2.95%, BaCO3 2.46%, SnO2 0.49%, and TiF3 1.7%.
[0075] Example 6
[0076] The low-melting-point antibacterial alkali-free glass of this embodiment includes the following components in mass percentage: SiO2 66.64%, Al2O3 10.78%, H3BO3 5.88%, MgO 4.9%, CaCO3 3.92%, Sr(NO)2 2.94%, BaCO3 2.45%, SnO2 0.49%, and TiF 32%.
[0077] Example 7
[0078] The low-melting-point antibacterial alkali-free glass of this embodiment includes the following components in mass percentage: SiO2 65.95%, Al2O3 10.67%, H3BO3 5.82%, MgO 4.85%, CaCO3 3.88%, Sr(NO)2 2.91%, BaCO3 2.43%, SnO2 0.49%, and TiF33%.
[0079] Example 8
[0080] The low-melting-point antibacterial alkali-free glass of this embodiment includes the following components in mass percentage: SiO2 65.28%, Al2O3 10.56%, H3BO3 5.76%, MgO 4.8%, CaCO3 3.84%, Sr(NO)2 2.88%, BaCO3 2.4%, SnO2 0.48%, and TiF 34%.
[0081] Example 9
[0082] The low-melting-point antibacterial alkali-free glass of this embodiment includes the following components in mass percentage: SiO2 64.59%, Al2O3 10.45%, H3BO3 5.7%, MgO 4.75%, CaCO3 3.8%, Sr(NO)2 2.85%, BaCO3 2.38%, SnO2 0.48%, and TiF 35%.
[0083] Example 10
[0084] The low-melting-point antibacterial alkali-free glass of this embodiment includes the following components in mass percentage: SiO2 66.98%, Al2O3 10.83%, H3BO3 5.91%, MgO 4.92%, CaCO3 3.94%, Sr(NO)2 2.95%, BaCO3 2.46%, SnO2 0.49%, TiF3 1%, and TiO2 0.5%.
[0085] Comparative Example 1
[0086] The low-melting-point antibacterial alkali-free glass of Comparative Example 1 includes the following components in percentage by mass: SiO2 68%, Al2O3 11%, H3BO 36%, MgO 5%, CaCO3 4%, Sr(NO)2 3%, BaCO3 2.5%, and SnO2 0.5%.
[0087] Comparative Example 2
[0088] The low-melting-point antibacterial alkali-free glass of Comparative Example 2 includes the following components in mass percentage: SiO2 64.26%, Al2O3 10.39%, H3BO3 5.67%, MgO 4.72%, CaCO3 3.78%, Sr(NO)2 2.83%, BaCO3 2.36%, SnO2 0.47%, and TiF3 5.5%.
[0089] Comparative Example 3
[0090] The low-melting-point antibacterial alkali-free glass of Comparative Example 3 includes the following components in mass percentage: SiO2 66.33%, Al2O3 10.37%, H3BO 37%, MgO 4.88%, CaCO3 3.9%, Sr(NO)2 2.93%, BaCO3 2.44%, SnO2 0.49%, and TiF3 1.3%.
[0091] Comparative Example 4
[0092] The low-melting-point antibacterial alkali-free glass of Comparative Example 4 includes the following components in mass percentage: SiO2 66.39%, Al2O3 10.74%, H3BO3 5.86%, MgO 4.88%, CaCO3 3.91%, Sr(NO)2 4%, BaCO3 2.44%, SnO2 0.49%, and TiF3 1.3%.
[0093] Comparative Example 5
[0094] The low-melting-point antibacterial alkali-free glass of Comparative Example 5 includes the following components in mass percentage: SiO2 66.43%, Al2O3 10.75%, H3BO3 5.86%, MgO 4.88%, CaCO3 3.91%, Sr(NO)2 2.93%, BaCO3 2.44%, SnO2 1.5%, and TiF3 1.3%.
[0095] The raw materials of Examples 1-10 and Comparative Examples 1-5 are accurately weighed in proportion and put into a mixer for uniform mixing. The mixed raw materials are sent into a high-temperature electric furnace, and the furnace temperature is set to 1600° C. for melting. The molten glass liquid is clarified to remove bubbles and impurities therein to ensure the quality of the glass. The clarified glass liquid is processed into glass sheets through overflow molding.
[0096] The performance tests were performed on the glasses of Examples 1-10 and Comparative Examples 1-5:
[0097] Melting point test of mixed raw material samples (differential thermal analysis method): 15 mg of the raw materials uniformly mixed in each embodiment and comparative example were taken and divided into three portions. The melting points were tested using a differential thermal analyzer and the average value was taken.
[0098] Transmittance test: Take three samples of the finished glass of each embodiment and comparative example, and use the standard transmittance test method (GB / T31370.1-2015) to test the transmittance of the glass samples at 400-800nm, and take the average value.
[0099] Refractive index: Take three samples of the finished glass of each embodiment and comparative example, measure the refractive index of the glass samples using a Michelson interferometer, and take the average value.
[0100] Thermal expansion coefficient test: Take three samples of the finished glass of each embodiment and comparative example, and use the standard thermal expansion coefficient test method (JIS R 3251:1995) to test the thermal expansion coefficient of the glass samples, and take the average value.
[0101] Softening point test: Take three samples of the finished glass of each embodiment and comparative example, and use the standard softening point test method (ASTM C338-93 (2019)) to test the softening point of the glass samples, and take the average value.
[0102] Annealing point: Take three samples of the finished glass of each embodiment and comparative example, and use the standard annealing point test method (SJ / T11039-1996) to test the annealing point of the glass samples, and take the average value.
[0103] Strain point: Take three samples of the finished glass of each embodiment and comparative example, and use the standard strain point test method (KSL2505-2009) to test the strain point of the glass samples, and take the average value.
[0104] Young's modulus, shear modulus, and Poisson's ratio test: Take three portions of the finished glass of each embodiment and comparative example, and test the glass samples using the standard test method (GB / T 7962.6-2010 "Test methods for colorless optical glass Part 6: Young's modulus, shear modulus and Poisson's ratio") to take the average value.
[0105] Chemical stability test: Take three portions of the finished glass of each embodiment and comparative example, weigh and record the weight, then immerse the glass in a 20°C, 10% HF solution, take it out after 20 minutes, wash and dry it, calculate the weight loss per square centimeter, and take the average value.
[0106] Antibacterial performance test: Take glass samples of each embodiment and comparative example, with a size of 5 cm×5 cm and a thickness not exceeding 1 cm, and prepare 9 pieces of finished glass of each embodiment and comparative example as test samples for each bacterial species (all of which are sterilized, and the average number of active cells obtained directly after inoculation of 3 pieces of comparative example 1 glass, the average number of active cells obtained after inoculation of 3 pieces of comparative example 1 glass and placing for 24 hours, and the average number of active cells obtained after inoculation of 3 pieces of comparative example 1 glass and placing for 24 hours). The antibacterial performance of the glass samples is tested using the standard antibacterial test method (JIS Z 2801:2010).
[0107] Calculation of antimicrobial activity value: Calculate the antimicrobial activity value R according to the formula in JIS Z 2801:2010 standard. The formula is: AV = lg (B / A) – lg (C / A) = lg (B / C)
[0108] The calculation formula of antibacterial rate is:
[0109] Among them, A, B, and C are respectively the average number of active cells obtained directly after the glass slide of comparative example 1 was inoculated, the average number of active cells obtained after the glass slide of comparative example 1 was placed for 24 hours after inoculation, and the average number of active cells obtained after the glass slides of other embodiments and comparative examples were inoculated with the corresponding bacterial species and placed for 24 hours except comparative example 1 (unit: CFU / mL).
[0110] AV: indicates antimicrobial activity;
[0111] R: represents the antibacterial rate (unit: %).
[0112] The test results of glass properties of Examples 1-10 and Comparative Examples 1-5 are shown in Table 1-2:
[0113] Table 1 Glass performance test results of Examples 1-10
[0114]
[0115]
[0116] Table 2 Glass performance test results of comparative examples 1-5
[0117]
[0118]
[0119] It can be seen from Table 1 that compared with Comparative Example 1, Example 3 has a higher transmittance and other properties that are better than those of products on the market. After adding titanium trifluoride, the melting point of the raw material mixture is reduced by 186°C, indicating that titanium trifluoride has a significant fluxing effect; and the finished glass shows significant antibacterial effects on Staphylococcus aureus, Escherichia coli and mold, and the antibacterial rate reaches more than 97%, indicating that it has good antibacterial properties.
[0120] In addition, by Figure 1 It can be seen that since titanium trifluoride can decompose at high temperature and interact with other components to form low-melting-point fluorides, these fluorides can also reduce the viscosity of the glass liquid, promote the melting and mixing of the raw materials, and thus significantly reduce the melting point of the glass. Therefore, as the titanium trifluoride content increases, the melting point of the glass gradually decreases.
[0121] Depend on Figure 2 It can be seen that titanium trifluoride will cause enhanced absorption and scattering of light. The electrons in the titanium trifluoride molecules may interact with the incident light, causing part of the light to be absorbed. At the same time, the particles or uneven distribution of titanium trifluoride may also cause light scattering, reducing the amount of light passing through the glass, thereby reducing the transmittance.
[0122] The refractive index is related to the electronic polarizability of the glass, given by Figure 3 It can be seen that the addition of titanium trifluoride will change the electron cloud distribution of the glass, making it easier for electrons to be polarized under the action of the light field. This enhanced electron polarizability causes the propagation speed of light in the glass to slow down, thereby increasing the refractive index.
[0123] The coefficient of thermal expansion depends on the microstructure of the glass and the strength of the chemical bonds and is given by Figure 4 It can be seen that the addition of titanium trifluoride will affect the network structure of the glass and the interaction force between atoms, react with the components in the glass, shorten the bond length of the ionic and covalent bonds in the glass, and increase the bond energy, thereby making the glass structure tighter. This tight structure limits the movement space of atoms or ions when heated, so that thermal expansion is suppressed, which in turn leads to a decrease in the thermal expansion coefficient.
[0124] The softening point, annealing point and strain point of glass are all related to the structure and viscosity changes of glass. The titanium ions in titanium trifluoride can form strong chemical bonds with oxygen ions in glass and participate in the network structure of glass. Figure 5-7It can be seen that with the increase of titanium trifluoride content, the number of such chemical bonds increases, making the network structure of the glass denser and stronger, thereby improving the softening point, annealing point and strain point of the glass; but when the titanium trifluoride content is too high, its distribution in the glass is uneven, or its content is too high, resulting in local structural abnormalities, which will destroy the uniformity of the glass network. This uneven structure will reduce the softening point, annealing point and strain point of the glass.
[0125] Young's modulus reflects the material's ability to resist tensile deformation. Figure 8 It can be seen that the addition of titanium trifluoride makes the glass structure tighter and the chemical bonds stronger, so the Young's modulus may increase; conversely, if the amount is excessive, the glass structure will become loose and the Young's modulus may decrease.
[0126] The shear modulus is related to the material's ability to resist shear deformation, and the effect of titanium trifluoride on the glass structure will indirectly affect the shear modulus. Fig. 9 It can be seen that the addition of titanium trifluoride changes the microstructure of the glass, causing the shear resistance between atoms to change, and the shear modulus will change accordingly.
[0127] Poisson's ratio reflects the relationship between the transverse and longitudinal deformation of the material. Fig.10 It can be seen that the addition of titanium trifluoride changes the microstructure of the glass, affects the Young's modulus and shear modulus of the glass, and then changes the Poisson's ratio of the glass.
[0128] In addition, titanium trifluoride releases antibacterial ions, such as titanium ions and fluoride ions, which interact with the cell membranes or internal structures of bacteria and fungi, destroying their physiological functions, thereby achieving an antibacterial effect. Figure 12-13 It can be seen that as the content of titanium trifluoride increases, the amount of antibacterial ions released increases, and the antibacterial rate increases accordingly. Example 10 adds 0.5% of nano titanium dioxide as an antibacterial enhancer, so Example 10 introduces a total of 1.5% of titanium ions, and the amount of fluoride ions is the same as Example 4, which is 1%. Figure 1-12 It can be seen that the properties of the glass prepared in Example 10 are similar to those in Example 4. Fig.13 It can be seen that compared with Example 2, the antibacterial rate of the glass in Example 10 against Staphylococcus aureus is increased by 1.31%, the antibacterial rate against Escherichia coli is increased by 2.73%, and the antibacterial rate against mold is increased by 2.87%; while in Comparative Examples 3-5, which add the same amount of titanium trifluoride as in Example 3, only the content of other key components is changed, and the antibacterial rate of the glass is not significantly affected.
[0129] Compared with the comparative example 1 without adding titanium trifluoride, the melting point of the raw material mixture and various properties of the finished glass product of the embodiment 3 with adding an appropriate amount of titanium trifluoride are significantly improved, which proves that adding an appropriate amount of titanium trifluoride has an optimizing effect on the performance of the glass product.
[0130] In Comparative Example 2, an excess of titanium trifluoride was added. Figure 1-12 It can be seen that it has a positive effect on reducing the melting point of the raw material mixture and the thermal expansion coefficient, chemical stability and antibacterial rate of the glass. This is because the excess titanium trifluoride introduces more fluorine ions and titanium ions, which can further reduce the melting point, and can also shorten the bond lengths of more ionic bonds and covalent bonds in the glass and increase the bond energy, thereby making the glass structure tighter and reducing the thermal expansion coefficient; however, the excess titanium trifluoride has a greater negative effect on the softening point, annealing point, strain point, Young's modulus, shear modulus, transmittance and refractive index of the glass. This is because the excessive titanium trifluoride introduced is unevenly distributed in the glass, and its high content leads to local structural abnormalities, destroying the uniformity of the glass network, and causing the glass to have color and more defects.
[0131] Chemical stability reflects the performance of glass in resisting chemical reagents in downstream processes. Titanium ions can form strong chemical bonds with oxygen ions in glass, enhancing the connectivity and stability of the glass network structure. This enhanced connectivity makes the glass structure more stable and better able to resist chemical erosion. Fig.11 It can be seen that with the increase of titanium trifluoride content, the weight loss of glass after immersion in acid solution is smaller, and the chemical stability is stronger; after adding excessive boric acid in comparative example 3, the chemical stability of glass is significantly reduced, and the mass loss in acid solution increases by 2.82 mg / cm compared with that in example 3. 2 , which significantly reduces the strain point of the glass and impairs the acid resistance of the glass; and Figure 7 It can be seen that the strain point of the glass in Comparative Example 3 is 102°C lower than that in Example 3, indicating that adding excessive boric acid not only impairs the acid resistance of the glass, but also reduces the strain point.
[0132] Comparative Example 4 adds excess Sr(NO)2, from Figure 2 It can be seen that the transmittance of the glass in Comparative Example 4 is 9.84% lower than that in Example 3. Figure 3 It can be seen that the refractive index of the glass in Comparative Example 4 is 0.12 higher than that in Example 3. It can be seen that excessive Sr(NO)2 significantly reduces the optical properties of the glass, and more defects such as bubbles and stones appear in the glass.
[0133] Comparative Example 5 added an excess of SnO2. Figure 1 It can be seen that the melting point of the raw material mixture of Comparative Example 5 is 89°C higher than that of Example 3. Figure 2It can be seen that the transmittance of the glass in Comparative Example 5 is 8.08% lower than that in Example 3. Figure 3 It can be seen that the refractive index of the glass in Comparative Example 5 increases by 0.08, which shows that the excess SnO2 significantly increases the melting point of the raw materials and reduces the optical properties of the glass.
[0134] The present invention successfully prepares a glass with a low melting point and excellent antibacterial properties by adding an appropriate amount of titanium trifluoride as a flux and an antibacterial agent. The present invention not only reduces the glass manufacturing temperature, reduces energy consumption and production costs, but also increases the storage time of the product and reduces the quality risk in the downstream processing technology. The glass product of the present invention has broad application prospects in the fields of electronic display, touch screen, solar panel, etc.
Claims
1. Low melting point antibacterial alkali-free glass, characterized in that: The invention comprises the following components in percentage by mass: 60-75% silicon dioxide, 3-13% aluminum oxide, 3-6% boric acid, 1.5-5% magnesium oxide, 0.7-7.5% carbonate, 0.5-3% nitrate, 0.01-0.5% tin oxide, 0.1-5% titanium trifluoride and 0-1% antibacterial enhancer.
2. The low-melting-point antibacterial alkali-free glass according to claim 1, characterized in that: The antibacterial enhancer is nano silver particles or nano titanium dioxide.
3. The low-melting-point antibacterial alkali-free glass according to claim 1, characterized in that: The carbonate comprises 0.2-5% calcium carbonate and 0.5-2.5% barium carbonate.
4. The low-melting-point antibacterial alkali-free glass according to claim 1, characterized in that: The nitrate is strontium nitrate.
5. The method for preparing the low-melting-point antibacterial alkali-free glass according to claim 1, characterized in that: After the components are evenly mixed, they are sent into a high-temperature furnace for melting. After clarification, homogenization, molding and annealing, low-melting-point antibacterial alkali-free glass is obtained.
Citation Information
Cited By
Ultraviolet photosensitive alkali-free glass substrate and manufacturing method thereof
CN119859020A
Alkali-free ceramic glass for carbon dioxide laser TGV and preparation method thereof
CN119954390A
Method for preparing alkali-free glass based on low-value mineral raw materials and solid wastes
CN121020979A
